Central exclusive diffractive production of K+K-K+K- via the intermediate [phi phi] state in proton-proton collisions - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2019)
We present a study of the exclusive pp→ppK+K−K+K− reaction at high energies. We consider diffractive mechanisms with the intermediate ϕϕ state with its decay into the K+K−K+K− system. We include the ϕ(1020) ^t/^u-channel exchanges and the f2(2340) s-channel exchange mechanism. This f2 state is a candidate for a tensor glueball. We discuss the possibility to use the pp→ppϕϕ process in identifying the Odderon exchange. An upper limit for the POϕ coupling is extracted from the WA102 experimental data. The amplitudes for the processes are formulated within the tensor-Pomeron and vector-Odderon approach. We adjust parameters of our model to the WA102 data and present several predictions for the ALICE, ATLAS, CMS, and LHCb experiments. Integrated cross sections of order of a few nb are obtained, including the experimental cuts relevant for the LHC experiments. The distributions in the four-kaon invariant mass, rapidity distance between the two ϕ mesons, special “glueball filter variable,” and proton-proton relative azimuthal angle are presented. The distribution in rapidity difference of both ϕ-mesons could shed light on the f2(2340)→ϕϕ coupling, not known at present. We discuss the possible role of the f0(2100), η(2225), and X(2500) resonances observed in the ϕϕ channel in radiative decays of J/ψ. Using typical kinematic cuts for LHC experiments, we find from our model that the Odderon-exchange contribution should be distinguishable from other contributions for large rapidity distance between the ϕ mesons and in the region of large four-kaon invariant masses. At least, it should be possible to derive an upper limit on the Odderon contribution in this reaction.
Im Titel sind die Zeichen "+" und "-" hochgestellt
Im Titel ist "phi" als griechischer Buchstabe dargestellt
Gesehen am 11.07.2019